Should physical laws be unit-invariant?. (April 2020) - Grozier, Jim
Highlights: Unit-dependent formulae are common in the scientific literature. These formulae are often valid only in outdated unit systems. Such formulae are often used without stipulating their limited validity. They have survived partly because they simplified calculations. Flawed unit-based arguments can lead to error.